Cloning, genetic mapping, and expression analysis of an Arabidopsis thaliana gene that encodes 1-aminocyclopropane-1-carboxylate synthase. - Van der Straeten, D (1992)
A genomic clone of one member of the Arabidopsis thaliana (L.) Heynh. 1-aminocyclopropane-1-carboxylate (ACC) synthase (S-adenosyl-L-methionine methylthioadenosine-lyase, EC 4.4.1.14) gene family (AT-ACC1) was isolated and sequenced. A region of homology was found in the 5'-untranslated region with the promoter of a zucchini and a tomato ACC synthase gene. Comparison of its primary structure with other ACC synthases revealed conservation of seven peptide regions as well as similarity with 11 amino acids of the catalytic site of aminotransferases. Genomic DNA gel blotting suggested the existence of an ACC synthase multigene family in Arabidopsis, possibly with three other members, none of which is very closely related to AT-ACC1. The existence of at least one other gene was confirmed by the isolation of a cDNA (AT-ACC2) from a flower-specific cDNA library. The AT-ACC1 gene was mapped on the Arabidopsis restriction fragment length polymorphism map and is located on the top of chromosome 1. This position does not correspond to any known mutation on the genetic map. Expression of the AT-ACC1 gene was studied by reverse transcription-PCR on total RNA. Messenger accumulation was strong in young leaves and flowers. The gene was not induced by wounding of young leaves or in seedlings in the presence of auxin. Ethylene exposure of mature plants led to an induction of AT-ACC1 gene expression. It is suggested that AT-ACC1 protein has a role in developmental control of ethylene synthesis.